Syntactic perspectives on directive speech acts : a contrastive study - Freudinger, Markus
This thesis is situated in the field of contrastive pragmatics and compares the syntactic realizations of equivalent directive speech acts in English and German. The term directive speech act is being used in a more narrow sense than intended by Searle (1975).Dramatic plays are used as data source for the original language and the translation into the other language. The four texts are Brechts “Mutter Courage und Ihre Kinder“, Dürrenmatts „Die Physiker“, Osbornes „Look Back in Anger“, and Leighs „Abigail‘s Party“.The central questions of this study are: Which forms are available in each language? Which specific function does a form fulfill in the system of each language? How do forms correspond across languages?In general, realizations as regular sentences, irregular sentences and non-sentences are possible. In the case of regular sentences, the subcategories imperative, declarative, yes-no interrogative, and wh-interrogative are possible in both languages. German also offers the adhortative and the infinitive. There are remarkable differences in terms of frequencies for these types.In general, German and English behave rather similar in their use of the clause types. The detailed qualitative description of specific examples constitutes the main part of the analysis and answers the following questions: which forms occur as equivalences? Under which conditions can declaratives and interrogatives be used directively?Non-sentences also play an important role. Formal categories, however, are not helpful; hence the utterances were grouped according to functional aspects. These are: propositional content, relationship between speaker and hearer, and illocutionary force.

Scientiﬁc Literature Retrieval based on Terminological Paraphrases using Predicate Argument Tuple - Choi, Sung-Pil; Song, Sa-kwang; Jung, Hanmin; Geierhos, Michaela; Myaeng, Sung Hyon (Information Science and Industrial Applications: Proceedings, International Conference, ISI 2012, Cebu, Philippines, May 2012)
The conceptual condensability of technical terms permits us to use them as effective queries to search scientific databases. However, authors often employ alternative expressions to represent the meanings of specific terms, in other words, Terminological Paraphrases (TPs) in the literature for certain reasons. In this paper, we propose an effective way to retrieve “de facto relevance documents” which only contain those TPs and cannot be searched by conventional models in an environment with only controlled vocabularies by adapting Predicate Argument Tuple (PAT). The experiment confirms that PAT-based document retrieval is an effective and promising method to search those kinds of documents and to improve terminology-based scientific information access models.

A Proof-of-Concept of D³ Record Mining using Domain-Dependent Data - Lee, Yeong Su; Geierhos, Michaela; Song, Sa-Kwang; Jung, Hanmin (Software Technology: Prooceedings, International Conference, SoftTech 2012, Cebu, Philippines, May 2012)
Our purpose is to perform data record extraction from onlineevent calendars exploiting sublanguage and domain characteristics. We therefore use so-called domain-dependent data (D³) completely based on language-specific key expressions and HTML patterns to recognize every single event given on the investigated web page. One of the most remarkable advantages of our method is that it does not require any additional classification steps based on machine learning algorithms or keyword extraction methods; it is a so-called one-step mining technique. Moreover, another important criteria is that our system is robust to DOM and layout modifications made by web designers. Thus, preliminary experimental results are provided to demonstrate proof-of-concept of such an approach tested on websites in the German opera domain. Furthermore, we could show that our proposed technique outperforms other data record mining applications run on event sites.

Customer Interaction Management goes Social: Getting Business Processes plugged in Social Networks - Geierhos, Michaela; Ebrahim, Mohamed (Computational Social Networks: Tools, Perspectives and Applications)
Within this chapter, we will describe a novel technical service dealing with the integration of social networking channels into existing business processes. Since many businesses are moving to online communities as a means of communicating directly with their customers, social media has to be explored as an additional communication channel between individuals and companies. While the English-speaking consumers on Facebook are more likely to respond to communication rather than to initiate communication with an organisation, some German companies already have regularly updated Facebook pages for customer service and support, e.g. Telekom. Therefore, the idea of classifying and evaluating public comments addressed to German companies is based on an existing demand. In order to maintain an active Facebook wall, the consumer posts have to be categorised and then automatically assigned to the corresponding business processes (e.g. the technical service, shipping, marketing, accounting, etc.). This service works like an issue tracking system sending e-mails to the corresponding person in charge of customer service and support. That way, business process management systems which are already used to e-mail communication can benefit from social media. This allows the company to follow general trends in customer opinions on the Internet; moreover it facilates the recording of two-sided communication for customer relationship management and the company’s response will be delivered through consumer’s preferred medium: Facebook.

Talking like a book. Investigating colloquialization as a change in written English - Mindt, Ilka (Oralité(s) et écriture(s))

Change in Contemporary English. A Grammatical Study - Mindt, Ilka; Leech, Geoffrey; Hundt, Marianne; Mair, Christian; Smith, Nicholas (Archiv für das Studium der neueren Sprachen und Literaturen 164: 249: 2)

Tagungsbericht: Symposium für Promovierende der Fremdsprachen in der Endphase – \textquotedblEndspurt für Dis(s)orientierte\textquotedbl - Armbrust, Laura; Rumlich, Dominik (Zeitschrift für Fremdsprachenforschung)

The effects of CLIL: Students’ linguistic accuracy in relation to internal and external learner variables - Rumlich, Dominik (Language learning and language use)

(Sprach-)Tests in der Praxis: Die Studie „Development Of North Rhine-Westphalian CLIL Students“ (DENOCS). - Rumlich, Dominik (Fremdsprachenunterricht empirisch erforschen. Grundlagen - Methoden - Anwendung)

Victorian Values in Nineteenth- and Twenty-First-Century Advertising and Consumer Practices - Strauß, Sara (anglistik & englischunterricht)

Facets of Children’s Fears in Twentieth- and Twenty-First-Century Stream-of-Consciousness Fiction - Strauß, Sara (Who’s afraid of...? Facets of Fear in Anglophone Literature and Film)

Constructions of ‘Otherness’ in Frances Hodgson Burnett’s The Secret Garden - Strauß, Sara (A Hundred Years of The Secret Garden – Frances Hodgson Burnett’s Children’s Classic Revisited)

The Persistence of Modernism in Light (Critical Engagements: A Journal of Criticism and Theory: Special Section: Eva Figes)

Der Zauber Magischer Welten - Flotmann, Christina
Interview 11 Oct. 2012

Spatial Representations of British Identities

A Bricolage of Identities in Crisis. Colour Photography Documenting Northern England under Thatcher - Tönnies, Merle (Facteurs d'Identité / Faktoren der Identität)

Second-Person Narration in Literary and Conversational Storytelling - Mildorf, Jarmila (Storyworlds)

Imaginary Dialogues in English: Explorations of a Literary Form

New Perspectives on Imaginary Dialogues: An Interdisciplinary Dialogue - Kinzel, Till; Mildorf, Jarmila (Imaginary Dialogues in English: Explorations of a Literary Form)

Polite Conversation, Implicatures, and Comical Effect: Jonathan Swift and P. G. Wodehouse - Mildorf, Jarmila (Imaginary Dialogues in English: Explorations of a Literary Form)